Causes and pathways of land change in Southern Africa during the past 300 years.: Moving from simplifications to generality and complexity - Geist, Helmut J. (ERDKUNDE, 2002)
Progress in integrated land change science, especially the modelling of coupled human-environment conditions, suffers from the lack of a systematically generated and readily comparable documentation of trajectories of land use and land cover change. Taking the case of Southern Africa, two recent estimates of historical land change in the region are presented, together with indicative cause explorations inherent to them (cropland and pasture expansion). For selected classes of land change (deforestation, woodland degradation, ’desertification’, rangeland modification), major simplifications or ’myths’ are presented and held against qualitatively derived pathways of land change. It is further argued that a (semi)quantitative understanding of cause-connections is important, and that fast-track data can be generated from a meta-analysis of proximate causes (e.g., agricultural expansion) and underlying driving forces (e.g., market forces, policies, human population dynamics). However, the systematic exploration of case studies of land change is just a fast-track measure and first step towards the identification of robust cause-connections so as to better inform original case study research protocols (and the modelling community). Besides generalising from cases, a more complex framework for a causative factor and trajectory analysis is suggested, which extends beyond the proximate/underlying divide, including properties of systems dynamics (e.g., feedbacks) and vulnerability (e.g., resilience).